Rapid microbial detection model system in UHT milk products using poly(L-Lactic Acid) (PLLA) thin film - Nurul Hidayah Yusof,; Norrakiah Abdullah Sani,; Farah Hannan Anuar,; Mohd Suzeren Jamil,; Saiful Irwan Zubairi, (Penerbit Universiti Kebangsaan Malaysia, 2018)
Ultra-high temperature is a process that involves heating of milk to a very high temperature to produce sterile milk products. However, food poisoning due to consumption of UHT milk still happen in Malaysia. This study was done to develop a film that is made by poly(L-lactic acid) (PLLA) to detect the presence of microorganisms in UHT milk products. UHT milk that was used in this study was full cream milk. Contaminated milk that contained Bacillus cereus was made to conduct a model system on the relationship between colony forming unit of microorganisms and contact angle. Contaminated milk was also used as a control sample to study the difference of milk properties between fresh and contaminated milk. Physicochemical analysis (Brix, colour, pH and contact angle) and microbiological analysis (total plate count) were done to UHT milk sample as soon as the packaging of the milk was unsealed. Analysis was done with 30 min time interval until 4 h and 30 min since the unsealing of packaging. The results showed that presence of microorganisms in UHT milk was detected after the milk product was unsealed and exposed to environment for 3 h and 30 min. Contact angle resulted from the presence of microorganisms in UHT milk was 64.34 - 65.44° with its colony forming unit, 2.1 – 3.9 cfu/mL. Therefore, the potential usage of contact angle on PLLA thin film with respect to colony forming unit (cfu) in detecting the presence of microorganisms in UHT milk product was attained and well modelled.